2018
DOI: 10.29037/ajstd.495
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fluorescence in situ hybridization-Flow cytometry (FISH-FCM) technique to detect and quantify Vibrio cholerae population from different geographic regions

Abstract: Rapid and species-specific detection, and quantification of pathogenic bacteria are fundamental for monitoring and assessment of the risk they pose to any ecosystem. The study employed Vibrio cholerae, a human pathogen responsible for the life-threatening diarrhoeal disease, cholera and one among the most unwanted from marine bioinvasion point of view. The present study coupled fluorescence in situ hybridization (FISH) technique, a powerful tool in molecular phylogenetic discrimination, with flow cytometry (FC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The Fluorescence In-Situ Hybridization (FISH) allows the molecular phylogenetic discrimination and identification of specific bacteria within environmental samples. The coupling of FISH and FCM techniques can detect specific pathogens in the environmental samples and have been used recently for detecting and quantifying Vibrio cholerae populations from different geographic regions (Khandeparker et al 2018). The genetics of uncultured microorganisms, metagenomics, is also emerging as a powerful tool (Khandeparker et al 2017b).…”
Section: Resultsmentioning
confidence: 99%
“…The Fluorescence In-Situ Hybridization (FISH) allows the molecular phylogenetic discrimination and identification of specific bacteria within environmental samples. The coupling of FISH and FCM techniques can detect specific pathogens in the environmental samples and have been used recently for detecting and quantifying Vibrio cholerae populations from different geographic regions (Khandeparker et al 2018). The genetics of uncultured microorganisms, metagenomics, is also emerging as a powerful tool (Khandeparker et al 2017b).…”
Section: Resultsmentioning
confidence: 99%
“…The results of these studies are reported by Khandeparker et al (2018) and Lim et al (2018) in this volume.…”
Section: Port and Ballast Water Sampling; Fouling Panel And Bacterialmentioning
confidence: 76%
“…However, most studies dealing with FISH for water samples have focused on seawater and lake water samples. Here, FISH methods with tyramide signal amplification and without tyramide signal amplification have been applied [ 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 ].…”
Section: Specific State-of-the-art Flow-fish Methods and Applications For Monitoring And Detectionmentioning
confidence: 99%
“…However, most studies dealing with FISH for water samples have focused on seawater and lake water samples. Here, FISH methods with tyramide signal amplification and without tyramide signal amplification have been applied [166][167][168][169][170][171][172][173][174]. For air-related applications, the natural load of bioaerosols in swine barns and buildings was successfully characterized using FISH [80,175,176].…”
Section: Flow-fish In Water and Bioaerosolsmentioning
confidence: 99%